Cyberpredators and their prey - Shapiro, Lauren R. (Boca Raton, FL : CRC Press, 2023)
"The online environment has emerged as a continuous and unfettered source of interpersonal criminal activity beyond physical boundaries. Cyberpredators commit their crimes by employing the Internet and online services-social network platforms, online groups and organizations, smart phone apps, bulletin board systems, online forums, websites, internet relay chat channels-to locate and harm victims of all ages through attacking, exploiting, humiliating, bullying, harassing, threatening, defrauding, and exhorting. Cyberpredators and Their Prey describes non-sexual and sexual interpersonal crimes-online romance scam, swatting, trolling, stalking, bullying, harassment, minor sexting, sexual trafficking, child sexual abuse material, sextortion, and image-based sexual abuse offenses. Each chapter contains: crime definition and relevant issues; typical cyberpredator, motives, and methods; typical victims and behaviors that make them targets; current criminal laws for prosecuting cybercrimes and assessment of their applicability and effectiveness as deterrents; the crime's impact on individual victims and society in general; and cybersecurity prevention and intervention strategies. Also covered are the unique challenges that the regulation, investigation, and prosecution of these cybercrimes pose to criminal justice and private security agents worldwide; the need for society to hold companies operating online responsible for their role in cybercrime; and how aspects of the online environment (i.e., anonymity, toxic disinhibition, de-individuation, inculpability) contribute to harmful and abusive interpersonal interaction, particularly when enacted by perpetrators as part of a group attack. Key features: Portrays material through multidisciplinary lens of psychology, criminal justice, law, and security Provides consistent, practical information about online criminals and victims Compares online to offline versions of the same crime Discusses adequacy of current laws for prosecuting cybercriminals Considers elements of the online environment that foster criminal activity Describes social engineering techniques Considers the role of intimate partner violence in cybercrimes Reviews 21st century skills needed to educate and protect potential targets Cyberpredators and Their Prey will prove essential reading to those who are studying to become, or are currently, security professionals; law enforcement personnel and investigators; intelligence agents; private investigators; lawyers; compliance officers; social service workers; and other professionals who deal with interpersonal cybercrime through the lens of social science"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer crimes; Computer crimes -- Prevention; Internet -- Security measures; Internet -- Psychological aspects; Social media -- Moral and ethical aspects; COMPUTERS / Security / General; SOCIAL SCIENCE / Criminology; LAW / Forensic Science